2013
DOI: 10.3947/ic.2013.45.3.315
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Features of Post-Transplant Bloodstream Infection: An Analysis of 222 Consecutive Liver Transplant Recipients

Abstract: BackgroundBloodstream infection (BSI) is a significant cause of morbidity and mortality in liver transplant (LT) recipients. This study aimed to investigate the epidemiology and clinical features of post-transplant BSI in LT recipients.Materials and MethodsThe microbiology, frequency, and outcome of post-transplant BSI in the first year after LT were retrospectively analyzed in 222 consecutive patients who had received liver transplants at a single center between 2005 and 2011. The risk factors for post-transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 25 publications
(32 reference statements)
5
49
0
Order By: Relevance
“…A previous study reported two cases of polyfungal infections (C. albicans and Candida glabrata) in 20 hospitalized patients with catheterrelated candidaemia; however, none of the C. parapsilosis complex species was involved in polyfungal infections (Escribano et al, 2014). It has been reported that polymicrobial BSIs are strongly associated with increased mortality (Kim et al, 2013). Although there is no study to date regarding the survival of patients infected with C. parapsilosis and C. orthopsilosis, the identification of BSI due to more than one species is of extreme importance.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study reported two cases of polyfungal infections (C. albicans and Candida glabrata) in 20 hospitalized patients with catheterrelated candidaemia; however, none of the C. parapsilosis complex species was involved in polyfungal infections (Escribano et al, 2014). It has been reported that polymicrobial BSIs are strongly associated with increased mortality (Kim et al, 2013). Although there is no study to date regarding the survival of patients infected with C. parapsilosis and C. orthopsilosis, the identification of BSI due to more than one species is of extreme importance.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, 50.7% of the LTRs had a blood stream infection, 22.5% had pneumonia, and 14.0% had a urinary tract infection. It has been explained in the literature that the primary source in LTRs with blood circulation infection was abdominal or wound infection at the rate of 28.1% and biliary tract infection at the rate of 36.2% in the first year after transplantation [15]. In our study, only 1 patient had biliary complications within 30 days after transplantation.…”
Section: Discussionmentioning
confidence: 43%
“…Kim et al [15] also emphasized that reoperative episodes were meaningful risk factors for BSI. In spite of being pointed out that reoperation was a risk for infections, its effect on the treatment has not been mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…In the first few weeks after transplantation, joint infections are often hematogenous and caused by health-care-associated pathogens such as S. aureus (including MRSA) and gram-negative bacilli including P. aeruginosa [85,86]. However, in the months following transplantation, as patients are maintained on immunosuppressive therapy, they are more prone to infections caused by fungi and mycobacteria.…”
Section: Microbiologymentioning
confidence: 99%